Preliminary Investigations on the Therapeutic Efficacy and Safety of Mixed Probiotic Lactic Acid Bacteria on Albino Rats Challenged with Shigella dysenteriae - Adaeze Ngozi Ibejekwe; John Otumala Egbere; Michael Macvren Dashen; Anayochukwu Chibuike Ngene; Shawon Fredrick Akpagher; Joshua Ayobami Adetunji; Michael Eshioramhe Paul; Steve Kunle Oyero; Francis C. Udeozor; Yusuf A. Agabi; Pauline Ikpa (Advanced Gut & Microbiome Research)
This study investigates the potential of lactic acid bacteria (LAB) from the Nigerian beverage “kunun zaki” as alternative therapeutic agents against Shigella dysenteriae infections. In light of rising antibiotic resistance, the decline in probiotic usage prompted interest in LAB’s role in countering bacterial dysentery. Shigella dysenteriae, a significant cause of dysentery in developing nations, prompted this research which aims to carry out a preliminary investigation on the therapeutic efficacy and safety of mixed probiotic lactic acid bacteria on albino rats challenged with Shigella dysenteriae. Lactic acid bacteria, known for treating infections, were isolated from the beverage and tested against Shigella dysenteriae. The study employed 15 albino rats for in vivo trials, inducing diarrhea and treating with Lactococcus lactis and Lactobacillus brevis separately (T1 and T2) and combined in a 1 : 1 ratio (T3). Clinical parameters were observed before and after treatment. This revealed that L. lactis and L. brevis administration lowered rectal temperature from an average of 42°C caused by infection to 36.5°C. Stool consistency improved from light brown loose to dark brown semisolid, signifying reduced diarrhea. Bacteriological analysis displayed significant reduction (p<0.05) in Shigella counts in rat intestines across all treatments—220±2.88 CFU/g to 19.00±1.77 CFU/g, 8.33±0.88 CFU/g, and 65.00±2.88 CFU/g for T1, T2, and T3, respectively. The mixed LAB treatment was notably effective. Lactic acid bacteria counts increased significantly in Shigella-treated rats versus the positive control. Hematology and liver function parameters showed no significant differences between treatments and untreated controls. Lactic acid bacteria from “kunun zaki” exhibited curative potential, individually or combined, against Shigella dysenteriae. These lactic acid bacteria also positively influenced gut microbiota in Shigella-infected albino rats.